Establishment of human OCT4 as a putative HSP90 client protein: a case for HSP90 chaperoning pluripotency - Sterrenberg, Jason Neville (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
The therapeutic potential of stem cells is already being harnessed in clinical trails. Of even greater therapeutic potential has been the discovery of mechanisms to reprogram differentiated cells into a pluripotent stem cell-like state known as induced pluripotent stem cells (iPSCs). Stem cell nature is governed and maintained by a hierarchy of transcription factors, the apex of which is OCT4. Although much research has elucidated the transcriptional regulation of OCT4, OCT4 regulated gene expression profiles and OCT4 transcriptional activation mechanisms in both stem cell biology and cellular reprogramming to iPSCs, the fundamental biochemistry surrounding the OCT4 transcription factor remains largely unknown. In order to analyze the biochemical relationship between HSP90 and human OCT4 we developed an exogenous active human OCT4 expression model with human OCT4 under transcriptional control of a constitutive promoter. We identified the direct interaction between HSP90 and human OCT4 despite the fact that the proteins predominantly display differential subcellular localizations. We show that HSP90 inhibition resulted in degradation of human OCT4 via the ubiquitin proteasome degradation pathway. As human OCT4 and HSP90 did not interact in the nucleus, we suggest that HSP90 functions in the cytoplasmic stabilization of human OCT4. Our analysis suggests HSP90 inhibition inhibits the transcriptional activity of human OCT4 dimers without affecting monomeric OCT4 activity. Additionally our data suggests that the HSP90 and human OCT4 complex is modulated by phosphorylation events either promoting or abrogating the interaction between HSP90 and human OCT4. Our data suggest that human OCT4 displays the characteristics describing HSP90 client proteins, therefore we identify human OCT4 as a putative HSP90 client protein. The regulation of the transcription factor OCT4 by HSP90 provides fundamental insights into the complex biochemistry of stem cell biology. This may also be suggestive that HSP90 not only regulates stem cell biology by maintaining routine cellular homeostasis but additionally through the direct regulation of pluripotency factors.
Keywords: Induced pluripotent stem cells; Heat shock proteins; Stem cells; Transcription factors; Molecular chaperones